ANALISIS PENGARUH MAKRO EKONOMI TERHADAP RETURN SAHAM PERUSAHAAN PADA SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Feeriska Budi Wiranti; Idah Zuhroh; Ida Nuraini (Jurnal Ilmu Ekonomi JIE, 2019)
This study examines the stock returns of 14  food and beverage companies listed on the Indonesia Stock Exchange in 2017. The sampling technique used purposive sampling sample has certain criteria. The analysis tools multiple linear regression using panel data. In equation model, the stock return is the dependent variable, while the inflation rate and economic growth is the independent variable. The research results showed that simultaneously (Test F) all independent variables affect the dependent variable with a significant value of 0.0000. While partially (T-Test), independent variable X1 has a negative and significant influence on the dependent variable Y. While X2 has a negative and significant influence on the dependent variable Y. While X3 has, a negative and significant influence on the dependent variable Y. Determination Coefficient (R2) from the regression results of 0.212113 showed the ability of independent variables has explained the change of dependent variable of 21.21%,  while the rest of 78.79% has explained by other variables outside fro this research.